Correlation of Eye and Foot Coordination with Dribbling Ability in a Football Game - Tri Putra, Muh. Untung; Saman, Abdul; Jud, Jud; Rusli, Muhammad (Jurnal Pendidikan Jasmani (JPJ), 2024)
The aim of this research is to determine the correlation between eye-foot coordination and dribbling ability in the game of soccer. The population in this study were all students of SMA Negeri 1 Wiwirano, totaling 290 students consisting of 143 men and 147 women. The sampling technique used purposive random sampling, namely based on consideration of the gender of men, numbering 143 people and who could do dribbling well. OK, and after that it was randomized, namely at random, so that there were 30 samples in this study. The instrument used in this research is the soccer wall volleyball test to measure dribbling ability. Meanwhile, for dribbling skills in soccer games, use the dribbling test. Data analysis used descriptive statistics, normality tests, linearity tests, and hypothesis testing using correlation tests with the help of SPSS version 20. The research results showed that there was a positive relationship between the coefficient of the coordination variable and dribbling ability, with an r value of 0.961 and a significance level of 0.000 < 0 .05. The coefficient of determination was calculated at 0.924, or 92%, indicating that dribbling ability is significantly related to eye-foot coordination.